(untitled) (Research, Society and Development, 2021)
The objective in the diagnosis of Urinary Tract Infection Research (ITU) in order to correlate the urinalysis and urine culture with antibiogram presented in original papers, allowing pharmacotherapy analysis. Results from a study in accordance with the guidelines of the PRISMA protocol, performed in the period comprising July 2015 to September 2016, it is a literature review of qualitative and quantitative nature. Accordingly, the results showed the main etiological agent Escherichia coli, obtaining an average of 57.5% of confirmed infections with resistance to the antibiotic ampicillin in 61% of antibiograms performed, with a higher prevalence in females, considering most susceptible groups pregnant women and the elderly. However, the urinalysis is considered an examination low cost and first line available in the investigation of suspected cases of UTI, however it is essential to perform the urine culture with antibiogrma by the resistance that uropathogens have developed antimicrobial (antibiotic) once the urine culture enables identification of the microorganism causing the infection and the antimicrobial susceptibility testing the selection of the bacteria has no resistance, enabling to adopt a best treatment.